Development of Virtual Reality-Based Learning Media on Support Insulator Maintenance (PDKB-TM) to Improve Students' Competence at PLN - Muhammad Aditya Firnanda; Djoko Laras Budiyo Taruno (Indonesian Interdisciplinary Journal of Sharia Economics (IIJSE), 2026)
This study aims to: (1) Produce virtual reality-based learning media for PDKB-TM pedestal insulator maintenance material to improve student competency at PLN. (2) Analyze the feasibility of virtual reality-based learning media for PDKB-TM pedestal insulator maintenance material to improve student competency at PLN. (3) Measure the effectiveness of virtual reality-based learning media for PDKB-TM pedestal insulator maintenance material to improve student competency at PLN. The research method used in this study is Research and Development (R&D) using the ADDIE model which is divided into 5 stages: Analyze, Design, Development, Implement, and Evaluate. The subjects in the study were PDKB-TM employees at PT. PLN (Persero) UP3 Palembang, 2 material experts from lecturers, 2 media experts from the Faculty of Electrical Engineering, Yogyakarta State University. The learning media was tested on 30 students, with data collected through user response questionnaires as well as pretests and posttests. Data analysis was carried out by assessing the questionnaire using a Likert scale of 1-4, then a feasibility and effectiveness test was carried out using the normalized N-Gain test to determine the level of feasibility and effectiveness of the learning media. The results of the study are in the form of (1) Virtual reality-based learning media, (2) Guidebooks containing teaching materials, operating guides for virtual reality-based learning media and maintenance work instructions for PDKB-TM supporting insulators. The results of the material expert assessment were declared worthy with the category of "very good" obtaining a percentage of 86.52%, the results of the media expert assessment were declared worthy with the category of "very good" obtaining a percentage of 80.95%, and user responses received a very good category with a percentage of 91.1%. The results of the N-gain Test with a good category of 82.82%. Suggestions for developing virtual reality learning media with more PDKB-TM competency materials at PLN.